EVALUASI PRODUK E-BANKING BANK SYARIAH: MERESPON KEINGINAN DAN KEBUTUHAN NASABAH SECARA EFEKTIF UNTUK MENINGKATKAN KUALITAS PRODUK - Septin Puji Astuti; Wulan Al Fitra; Eko Setiawan (Media Riset Bisnis & Manajemen, 2012)
Considering the importance of customer-based improvement, the current paper presents the evaluation of Shar-E, an electronical banking product of Bank Muamalat Indonesia, by using fuzzy quality function deployment (QFD). From this research, it can be concluded that the availability of Automated Teller Machine (ATM) are the most important factor wanted by the customer to be present. Subsequently, providing good online systems such as network, banking transaction by online, and safety of Shar-E are the most important activities that should be well developed by BMI in order to respond to customers' needs and wants.Keywords: e-banking, Customers' needs and wants, Fuzzy theory. Quality function deployment